The Importance of Fire Extinguishers in Healthcare Facilities (Literature Review) - Ahyar Wahyudi; Ardan; Rozada Alemania; Adrianus Ledak (Formosa Journal of Science and Technology, 2023)
This text discusses the importance of Fire Extinguishing Equipment in fire prevention within healthcare facilities. Through a literature review, the author explores the understanding of the significance of using Fire Extinguishers, which are an integral part of healthcare facility safety. Healthcare facilities, such as hospitals and laboratories, are equipped with advanced machinery, cutting-edge technology, and hazardous chemicals. In day-to-day operations, the use of electrical equipment like MRI machines and ventilators increases the electrical load, while the presence of flammable materials like medical oxygen makes it even more complex. Smith, Miller, and Hamilton's research highlights that fires in healthcare facilities not only result in material losses but also pose a real threat to patients with limited mobility or critical conditions. The success of Fire Extinguisher utilization depends on the collaboration of various components, including Fire Extinguisher maintenance, awareness campaigns, Fire Extinguisher usage training, and coordination among staff during fires to ensure the safety of all parties involved. Fire Extinguishers play a vital role as first-response tools when fires occur. However, to prevent fires in healthcare facilities, proper electrical installations, well-organized cables, and personnel safety must be considered. Further research is needed to identify factors that can reduce the fire risk in Healthcare Facilities. To enhance healthcare facility safety, the use of Fire Extinguishers and an understanding of risk factors should be integrated into a holistic prevention strategy.